Β‐glucan therapy converts the inhibition of myeloid‐derived suppressor cells in oral cancer patients. (13th March 2021) - Lo, Ya‐Wen; Lee, Alan Yueh‐Luen; Liu, Yi‐Ching; Ko, Hui‐Hsin; Peng, Hsin‐Hui; Lee, Hsiang‐Chieh; Pan, Pei‐Yao; Chiang, Chun‐Pin; Cheng, Shih‐Jung
Abstract: Objectives: The myeloid‐derived suppressor cells (MDSCs) frequently have a high expansion in cancer patients. This research explored whether administration of β‐glucan could increase anti‐tumor immunity in oral squamous cell carcinoma (OSCC) patients. Materials and Methods: This study evaluated the MDSC level of circulating blood as CD33 + /CD11b + /HLA‐DR ‐/low by flow cytometry in 30 healthy donors (HDs, group I), in 48 oral squamous cell carcinoma (OSCC) patients before and after 14‐day preoperative administration of β‐glucan (group II), and in 52 OSCC patients without taking β‐glucan (group III). Results: A significantly higher mean MDSC level was observed in 100 OSCC patients than in 30 HDs ( p < .001). There was a significant reduction of the mean MDSC level in group II patients after taking β‐glucan ( p < .001). Moreover, we discovered a significantly higher recurrence‐free survival (RFS) in group II than in group III patients ( p = .026). Finally, the multivariate Cox regression further identified the MDSC level ≤1% and administration of β‐glucan as more favorable prognostic factors for OSCC patients. Conclusion: Preoperative administration of β‐glucan can augment anti‐tumor immunity and increase RFS rate via subversion of suppressive function of MDSC in OSCC patients.